Kung Fu Panda, legends of awesomeness. The midnight stranger [videorecording (DVD)]. ([Publisher not identified], 2014)
When it comes to martial arts mastery, Po is definitely no lightweight. But protecting the Valley of Peace is a team effort, so together with the Furious Five: Tigress, Monkey, Mantis, Crane, and Viper, the power-packed panda is dedicated to fighting the fiercest and funniest criminals in all of China, even if he has to dress up as The Midnight Stranger!